Vaccinations and Infections Are Associated With Unrelated Antibody Titers: An Analysis From the German Birth Cohort Study LISA - Caputo, Mahrrouz; Raupach-Rosin, Heike; Karch, André; Borte, Michael; Lehmann, Irina; Liebert, Uwe Gerd; Standl, Marie; Heinrich, Joachim; Mikolajczyk, Rafael T. (Frontiers in Pediatrics, 2019)
ABSTRACT (202 words) The evidence for non-specific effects (NSE) of vaccinations on all-cause morbidity and mortality among children is growing. However, our understanding of the underlying mechanisms is still limited. One hypothesis is that NSE are mediated by antibody titers. We used data of 2,123 children from the population-based birth cohort study LISA conducted in Germany to explore whether routine childhood vaccinations and the individual infection history in the first two years of life are associated with unrelated antibody titers. We selected 19 exposures (infections and vaccinations) and investigated their association with levels of twelve IgG antibody titers at the age of two years. Based on univariable analyses (ANOVA), we identified 21 crude associations between exposures and titers (p-value <0.05), while eleven (95%-CI: 6, 17) spurious associations were expected due to multiple testing. In exploratory multivariable analyses, we observed associations between seven investigated IgG titers and ten exposures; either administered vaccines (e.g. higher anti-hRSV IgG titer in BCG-vaccinated children (regression-coefficient in standard-deviation-units: 0.38; 95%-CI: 0.12, 0.65)) or infections (e.g. higher anti-measles IgG titer in children with reported chickenpox (0.44; 95%-CI: 0.08, 0.80)). Our results indicate the existence of associations between immunogenic exposures and unrelated antibody titers. Further studies investigating the underlying immunological mechanisms are required.